Increased local DNA methylation disorder in AMLs with DNMT3A-destabilizing variants and its clinical implication - Dohoon Lee; Bonil Koo; Seokhyeon Kim; Jamin Byun; Junshik Hong; Dong-Yeop Shin; Choong-Hyun Sun; Jaesung Kim; Ji-Joon Song; Siddhartha Jaiswal; Sung-Soo Yoon; Sun Kim; et al. (Nature Communications)
Abstract The mechanistic link between the complex mutational landscape of de novo methyltransferase DNMT3A and the pathology of acute myeloid leukemia (AML) has not been clearly elucidated so far. Motivated by a recent discovery of the significance of DNMT3A-destabilizing mutations (DNMT3A INS) in AML, we here investigate the common characteristics of DNMT3A INS AML methylomes through computational analyses. We present that methylomes of DNMT3A INS AMLs are considerably different from those of DNMT3A R882 AMLs in that they exhibit increased intratumor DNA methylation heterogeneity in bivalent chromatin domains. This epigenetic heterogeneity was associated with the transcriptional variability of developmental and membrane-associated factors shaping stem cell niche, and also was a predictor of the response of AML cells to hypomethylating agents, implying that the survival of AML cells depends on stochastic DNA methylations at bivalent domains. Altogether, our work provides a novel mechanistic model suggesting the genomic origin of the aberrant epigenomic heterogeneity in disease conditions.